Evaluating PROMIS(®) applied cognition items in a sample of older adults at risk for cognitive decline. (January 2017) - Howland, Molly; Tatsuoka, Curtis; Smyth, Kathleen A.; Sajatovic, Martha
Abstract: PROMIS(®) Applied Cognition is a short self-assessment of cognitive abilities and concerns that eliminates the need for a trained rater and provides online question banks that can be uniformly used across health care providers. This 12-month prospective study of 281 elderly individuals evaluates self-perceptions of cognitive functioning in relation to objective cognition, or assessment by an external rater, and compares PROMIS® Applied Cognition Abilities and Concerns subsets with commonly used "legacy" instruments. PROMIS® correlated with objective legacy measures (the Mini-Mental State Examination [MMSE] and Saint Louis University Mental Status [SLUMS] examination), depression (measured with the Geriatric Depression Scale [GDS]), anxiety, and activities of daily living. PROMIS® and MMSE correlations remained after controlling for depression and anxiety. PROMIS® associated more strongly than MMSE with depression, highlighting the relationship between subjective cognitive deficit and depression. One-year changes in PROMIS® correlated with one-year changes in MMSE and GDS. The PROMIS® Abilities subset more strongly correlated with objective cognition, whereas the Concerns subset more strongly correlated with depression and activities of daily living. PROMIS® seems to be a reasonable prescreening tool to identify patients with cognitive decline or psychological distress. Highlights: PROMIS(®) Applied Cognition correlated modestly with objective cognition. PROMIS(®) Applied Cognition correlated strongly with depression. Changes in this scale correlated with changes in cognition and depression. The Abilities and Concerns subscales differed in their clinical correlations.